The use of the game in the teaching and learning process of the periodic table: evaluation of a regence stage intervention in chemistry (Research, Society and Development, 2020)
The use of Educational Games points out demands for researches that aim to deepen its benefits and its difficulties. Therefore, the study on this theme becomes relevant, as it can be a tool to be applied and problematized in the teaching and learning process. Following in this direction is that this work aimed to evaluate if the use of Didactic Games can contribute to the promotion of significant learning of scientific contents linked to the study of the Periodic Table, having the student as the protagonist in the construction of their knowledge. It presents a research of qualitative approach, based on the methodology of action research and data collection via questionnaires and field diaries. The research subjects were high school students from a state public school in the southern region of SC and teachers involved in guiding and supervising the supervised internship in chemistry. All experience was permeated by the perspective of critical pedagogy, as well as the understanding of the Didactic Games as a playful tool to the chemistry teaching. In the obtained results it was identified that the students were captivated by the playful character of the game, becoming active in the process of appropriation of the concepts involved either by the individual or group acting situations. The protagonism in the learning process generated greater interest in chemistry, a fact that could be corroborated by the appreciation of the teachers who followed the process of the internship interventions.